Implications of Extending the Village Head's Working Period on The Effectiveness of Village Government - Hidayat, Rahmad; Sari, Patma (Faculty of Law, Universitas Sembilanbelas November Kolaka, 2024)
This research aims to determine the implications of extending the Chief of Village’s time of office on the effectiveness of village government administration and what factors can influence the effectiveness of village government administration. This type of research is normative juridical research which seeks to solve problems by studying legal norms using Law in books or studies from relevant library materials. The results of this research show that firstly, extending the term of office of the Chief Village is completely irrelevant to the urgency of the need to improve Village government at this time so that it has no implications for the effectiveness of village government administration and continuity of development, the argument for extending the term of office is more like the subjective reasons of the Village Heads and tends to have a political nuance. Second, the fundamental factors that must be synchronized are the Village Head's leadership, partnership and collaboration with external parties and more substantial community participation and involvement. If these factors can be combined optimally then the effectiveness of village government administration will be created regardless of how long a village head has led.